2020
DOI: 10.3390/molecules25133030
|View full text |Cite
|
Sign up to set email alerts
|

Novel Treatment for Mitigating Condensate Bank Using a Newly Synthesized Gemini Surfactant

Abstract: Condensate accumulation in the vicinity of the gas well is known to curtail hydrocarbon production by up to 80%. Numerous approaches are being employed to mitigate condensate damage and improve gas productivity. Chemical treatment, gas recycling, and hydraulic fracturing are the most effective techniques for combatting the condensate bank. However, the gas injection technique showed temporary condensate recovery and limited improvement in gas productivity. Hydraulic fracturing is considered to be an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…There are several methods, which may help to overcome the condensate banking effect in well. Some approaches include the injection of solvents and chemicals to alter formation wettability to minimize condensate blockage [17][18][19]. A recent study [19] showed that developing a flowback system based on the formation of physical properties differentiation to control water phase invasion, and changing wettability or injecting thermochemical fluid to control condensate blocking are feasible methods to relieve liquid phase blockage damage in tight condensate reservoirs.…”
Section: Optimization Of Condensate Production Modementioning
confidence: 99%
See 1 more Smart Citation
“…There are several methods, which may help to overcome the condensate banking effect in well. Some approaches include the injection of solvents and chemicals to alter formation wettability to minimize condensate blockage [17][18][19]. A recent study [19] showed that developing a flowback system based on the formation of physical properties differentiation to control water phase invasion, and changing wettability or injecting thermochemical fluid to control condensate blocking are feasible methods to relieve liquid phase blockage damage in tight condensate reservoirs.…”
Section: Optimization Of Condensate Production Modementioning
confidence: 99%
“…These methods will lower the rate of pressure drop and permit the production of a single-phase gas. The most effective techniques for combatting the condensate bank are hydraulic fracturing and pumping the formation with dry gas [17,21] and chemical treatment with methanol [22] or novel developed surfactants [17,18].…”
Section: Optimization Of Condensate Production Modementioning
confidence: 99%
“…In fact, when the pressure of the reservoir falls below the dew point pressure, condensation starts, resulting in the formation of two phase profiles consisting of liquid and gas near the well bore zone . As a result, gas mobility reduces significantly compared to liquid condensation subsequently leading to less productivity in the gas condensate fields. To mitigate this problem, there are several approaches divided into the following three major techniques: The injection of chemicals such as solvents, inhibited diesel, inhibited dry gas, and wettability alteration chemicals can serve to reduce the effect of gas condensate blockage on the productivity of well. Gas recycling and the injection of carbon dioxide and nitrogen known as pressure maintenance techniques are implemented to increase the pressure of a reservoir (above the dew point) and enhance liquid recovery with the reduction of liquid dropout. Drilling horizontal wells, hydraulic fracturing, and matrix acidizing coupled with the mentioned former techniques improve the productivity of wells. …”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the generated fractures in turn cause a major problem. Actually, it is possible for the condensate to develop near the wellbore zone after a while of production . Restrepo et al conducted a trial study to apply chemicals in order to investigate the effect of fluorinated polymer on the rock wettability with the aim of enhancing both oil and gas permeabilities.…”
Section: Introductionmentioning
confidence: 99%